In Silico Inhibition of Essential Candida albicans Proteins by Arenicin, a Marine Antifungal Peptide - do Carmo Silva, Lívia; Marcelino Barbosa, Andreia; Pereira Tannous, Isabele; Gonzaga Santos, Thaynara; Santana de Curcio, Juliana; Nojosa Oliveira, Lucas; Garcia Silva, Marielle; Alves de Oliveira, Amanda; Melo Lima, Raisa; Santiago Freitas e Silva, Kleber (International Marine Science Journal, 2019)
Fungal infections increased substantially in the last years, becoming a relevant public health problem. Many of these infections account for high rates of morbidity and mortality. The emergence of resistant fungal clinical isolates have also motivate studies to find new antifungal therapies. Candida albicans is an oportunistic pathogen and affects a great number of immunocompromised patients worldwide. The marine ecosystem has been considered a rich source of bioactive metabolites due to the complexity and originality of its structures. Proteins and peptides from marine organisms have been shown to have antiviral, anti-inflammatory, antimalarial, anticancer, antimicrobial and antifungal properties. Arenicins are antimicrobial peptides isolated from the marine lugworm Arenicola marina with 21 amino acid residues in a β-hairpin structure. Dihydrofolate reductase, exo-b-(1,3)-glucanase and sterol 14α-demethylase are essential C. albincas enzymes that take part in DNA, cell wall and membrane metabolism, respectively. The present study evaluates the interaction of arenicin with important enzymes of C. albicans related to cell wall, ergosterol and DNA metabolism in order to elucidate possible molecular targets. We showed through an in silico approach, that a single compound from a marine worm (A. marina), can bind to three C. albicans essential proteins. The interaction occurs in regions inside the active site or at least near, with amino acid residues evaluated as hot spots. Arenicin is a new promising antifugal drug. The next step is to investigate protein-protein interactions performed by DHFR, EBG and CYP51 and assess whether arenicin is able to disrupt essential interaction or not.
Keywords: Arencin; marine antifungal peptide; small bioactive molecules